2017
DOI: 10.18632/oncotarget.15928
|View full text |Cite
|
Sign up to set email alerts
|

miR-29a regulated ER-positive breast cancer cell growth and invasion and is involved in the insulin signaling pathway

Abstract: Increasing amounts of evidence show that insulin can activate different insulin signaling pathways to promote breast cancer growth and invasion. miR-29a plays crucial roles in decreasing glucose-stimulated insulin secretion, as well as in regulating breast cancer cell proliferation and EMT. However, the mechanism responsible for the regulatory effects of miR-29a on breast cancer growth and invasion and the relationship between these effects and insulin signaling remains unclear. Herein, we showed that human in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 34 publications
(58 reference statements)
3
33
0
2
Order By: Relevance
“…IGF-1R is markedly and excessively expressed in breast cancer cells compared with normal breast epithelium and benign tumor tissues. Moreover, research has indicated that the IGF-1R expression level is related to the recurrence, metastasis and prognosis of breast cancer (15). The present study also revealed that overexpression of microRNA-320a suppressed IGF-1R, p-Akt and cyclin D1 protein expression, and induced Bax protein expression in MDA-MB-231 cells.…”
Section: Discussionsupporting
confidence: 69%
“…IGF-1R is markedly and excessively expressed in breast cancer cells compared with normal breast epithelium and benign tumor tissues. Moreover, research has indicated that the IGF-1R expression level is related to the recurrence, metastasis and prognosis of breast cancer (15). The present study also revealed that overexpression of microRNA-320a suppressed IGF-1R, p-Akt and cyclin D1 protein expression, and induced Bax protein expression in MDA-MB-231 cells.…”
Section: Discussionsupporting
confidence: 69%
“…Caspase promotes apoptosis, reconstructing the cytoskeleton, terminating DNA repair, destroying DNA and nuclear structure and reducing formation of the apoptotic body (23). Certain studies in biological chemistry and genetics have indicated that the caspase protease family has important functions at every stage of apoptosis (23,24). The results of the present study demonstrated that the downregulated expression of HOTTIP reduced cell viability, induced apoptosis, promoted caspase-3 and caspase-8 activity, and increased Bax expression in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 49%
“…MRE stands for microRNA recognition element. E. IPA comparison analysis between gene targets by highly and lowly modified miRNAs for pathways implied for cancer progression and migration, NFAT [59], Axonal Guidance [60], MYC Mediated Apoptosis [61], Protein kinase A [44], Pigment epithelium-derived factor (PEDF) [62], Thrombin [63], CXCR4 [43], Erythropoietin [64], Insulin receptor [65], FAK [66], STAT3 [67].…”
Section: Competing Interestsmentioning
confidence: 99%